Early management of columellar skin necrosis post-revision septorhinoplasty - Ayman Y Jaber; Osama A Jbarah; Leen R Shahin (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Background: Columellar skin necrosis is a rare complication of Septorhinoplasty procedures. However, it is more frequent in patients who undergo multiple revision procedures and have poor skin quality. Therefore, some patients require wound care immediately post-operation. Dressing of the columellar region is difficult due to the location and anatomical configuration.  Case presentation: In this paper, we present a case of partial necrosis of the columellar skin following an open Septorhinoplasty procedure which was noted on the first post-operative day. Improving circulation to the affected area was the key target of the treatment approach.  Conclusion: A topical hemoglobin-based oxygenating spray (Granulox, SastoMed GmbH, Georgsmarienhütte, Germany) was applied immediately on the columellar skin wound as it is a simple and easy dressing material and can lead to healing without obvious scarring. Key points Question: Would an early, minimally invasive intervention with a hemoglobin-based oxygenating spray in a patient who was diagnosed with partial columellar skin necrosis 24 hours post revision Septorhinoplasty - without the need for surgical management provide a satisfactory outcome?  Finding and meaning: The treatment yielded a good aesthetic outcome in a short duration with no significant side effects and demonstrated the ease of treating a difficult complication without the need for more surgeries.